Analysis of the Influence of Lubricant on Transmission Efficiency of Transmission Under NEDC Operating Condition - Mo Yimin; Dong Jixing; Wang Jun; Yin Kaifeng; Liang Wei (Jixie chuandong)
The transmission is a key part of the drive train,and it has a direct impact on the vehicle NEDC fuel consumption. In order to improve the NEDC integrated fuel consumption of a MPV model,a test method of transmission efficiency based on NEDC is proposed. The influence of different lubricating oil viscosity,temperature,additive and other factors on gearbox transmission efficiency is compared. The results show that the viscosity of lubricating oil is lower under NEDC,the transmission efficiency of transmission is higher.The decrease of the oil film thickness caused by the increase of oil temperature has greater influence on the transmission efficiency than that caused by the increase of the oil film thickness due to the increase of the rotation speed and the transmission efficiency of the transmission. The viscosity-temperature characteristic of lubricating oil viscosity enhances the viscosity-temperature characteristic of oil,The influence of transmission efficiency is greater than that of lubricating oil viscosity on transmission efficiency.